RURAL DEVELOPMENT AND GENERALIST SOCIAL WORK PRACTICE DURING THE FIRST YEARS OF TURKISH REPUBLIC - Murat BAYAR (Fırat University, 2020)
This humble work focuses on the rural development practice during the very first years of Turkish Republic. Accordingly, concepts such as “rural area” and “rural development” are discussed, and village institutes as practical examples of generalist social work practice that responds to the need for a holistic and multidimensional intervention during the rural development process are touched on. Although there is no single definition of “rurality” that affects a population’s way of working, solidarity and organization in a given area, “rural” in Turkey is believed to be characterized via various disadvantages. Practices of development are carried out to nullify the aforesaid disadvantages, and to reduce the poor and the poverty. Rural development is the totality of economic, social and humanitarian practices that are carried out in order to improve the living standards of people living in the rural areas which pays attention to the policies that leads to the exploitation of the resources and which favors sustainability. The success of this process depends on maintaining the participation of targeted ruralites that are expected to benefit from it, and on carrying out services that are proper to the structure and the needs. Handling problems and realizing the potentialities holistically in a given rural development area belongs to the role and the responsibilities of social work. In rural areas, generalist social work practice is preferred. The need for multi-information bodies and the insufficiency of specialized particular practices seem to be the reasons behind this choice. In order to produce a strong social work intervention in rural areas, there is need to reevaluate the practices of the past. To do so, the rural development policies of the early Turkish Republic and village institutes as an example of generalist social work practice are discussed. As a result, despite all the positive and negative critiques, village institutes of the early republic appear as a holistic rural development policy and a generalist social work practice.